2019
DOI: 10.1093/trstmh/trz005
|View full text |Cite
|
Sign up to set email alerts
|

Serological evidence for a decline in malaria transmission following major scale-up of control efforts in a setting selected for Plasmodium vivax and Plasmodium falciparum malaria elimination in Babile district, Oromia, Ethiopia

Abstract: Background Following successful malaria control during the last decade, Ethiopia instituted a stepwise malaria elimination strategy in selected low-transmission areas. Methods Cross-sectional surveys were conducted in Babile district, Oromia, Ethiopia from July to November 2017 to evaluate malaria infection status using microscopy and nested polymerase chain reaction (nPCR) and serological markers of exposure targeting Plasmodium falciparum an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…Overall, the wild type Pfcrt -K76 haplotype was detected in 23.7% (40/169) and the mutant Pfcrt -76T in 76.3% (129/169) of samples across sites. We observed a statistically significant difference in the prevalence of Pfcrt -76 codons among the study sites (P < 0.001): mutant ( Pfcrt -76T) type was virtually fixed in Babile (100%, 31/31) and with near fixation at Adama (98.4%, 61/62) districts of Oromia region where P. vivax is highly endemic (41.4% and 62.2% of cases, respectively) (Keffale et al, 2019; Tadesse et al, 2018). On the other hand, a higher prevalence of the wild type ( Pfcrt -K76) codon was found in Abobo and Lare districts of Gambella (58.5%, 31/53) and in Mao-Komo and Menge districts of Benishangul-Gumuz (34.8%, 8/23) (Table 1).…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Overall, the wild type Pfcrt -K76 haplotype was detected in 23.7% (40/169) and the mutant Pfcrt -76T in 76.3% (129/169) of samples across sites. We observed a statistically significant difference in the prevalence of Pfcrt -76 codons among the study sites (P < 0.001): mutant ( Pfcrt -76T) type was virtually fixed in Babile (100%, 31/31) and with near fixation at Adama (98.4%, 61/62) districts of Oromia region where P. vivax is highly endemic (41.4% and 62.2% of cases, respectively) (Keffale et al, 2019; Tadesse et al, 2018). On the other hand, a higher prevalence of the wild type ( Pfcrt -K76) codon was found in Abobo and Lare districts of Gambella (58.5%, 31/53) and in Mao-Komo and Menge districts of Benishangul-Gumuz (34.8%, 8/23) (Table 1).…”
Section: Resultsmentioning
confidence: 93%
“…Benishangul-Gumuz region, with Mao-Komo and Menge districts, is also P. falciparum dominated with relatively higher prevalence of P. vivax (10.1%) (Geleta and Ketema, 2016) and more seasonal transmission. The Oromia region study site districts of Babile and Adama are characterized by seasonal malaria transmission with co-endemicity for P. falciparum and P. vivax where P. vivax infections attributed to be 41.4% (Keffale et al, 2019) in the first and 62.2% (Tadesse et al, 2018) in the later district, respectively (Fig. 1 and Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…Most of these individuals (328/611) presented anti-PvAMA1 binding IgG, corresponding to 53.68% of the entire cohort. Among infected and non-infected individuals, the percentage of positive sera for anti-PvAMA1 binding IgG was significantly higher during the patent infection (80.77%) than in non-infected counterparts (49.72%) (p < 0.0001 -Figure 3A), confirming the immunogenicity of the PvAMA-1 protein during natural infections (Rodrigues et al, 2005;Morais et al, 2006;Wickramarachchi et al, 2006;Mufalo et al, 2008;Vicentin et al, 2014;Xia et al, 2015;Rosas-Aguirre et al, 2015;Salavatifar et al, 2015;Sańchez-Arcila et al, 2015;Kale et al, 2019;Keffale et al, 2019;Surendra et al, 2019). The prevalence of these antibodies significantly increased with age for either infected or noninfected individuals, ranging from 68.8%/38.5% in children and youngsters (0-20 years old) to 83.3%/56.3% in young adults (21-40 years old), respectively (noninfected 0-20 years old vs noninfected 21-40 years oldp < 0.05; infected 0-20 years old vs infected 21-40 years oldp < 0.05; infected 0-20 years old vs infected > 40 years oldp < 0.05 -Figure 3B).…”
Section: Resultsmentioning
confidence: 65%
“…Several studies characterizing the naturally acquired human immune responses to the PvAMA-1 ectodomain were performed in malaria endemic areas from Brazil ( Rodrigues et al., 2005 ; Morais et al., 2006 ; Múfalo et al., 2008 ; Vicentin et al., 2014 ; Sánchez-Arcila et al., 2015 ; Pires et al., 2018 ; Soares et al., 2020 ), Peru ( Rosas-Aguirre et al., 2015 ), Sri Lanka ( Wickramarachchi et al., 2006 ), India ( Kale et al., 2019 ), Ethiopia ( Keffale et al., 2019 ; Assefa et al., 2020 ), Indonesia ( Surendra et al., 2019 ), Iran ( Salavatifar et al., 2015 ) and other regions around the world ( Kim et al., 2003 ; Cook et al., 2010 ; Xia et al., 2015 ). These studies confirmed the high immunogenicity of this protein during infections, especially in regions with higher levels of disease transmission and in individuals with recent infections.…”
Section: Introductionmentioning
confidence: 99%
“…Two residents in Arjo consented to participating but did not complete the questionnaire or provide blood samples and were thus excluded from the study. The median age of participants was 27 years (interquartile range [IQR] 20-36) in Arjo and 28 years (IQR [23][24][25][26][27][28][29][30][31][32][33][34][35][36] in Gambella. The study population in Arjo was female biased (60.5%), whereas the inverse sex ratio was reported among participants in Gambella (60.1% male).…”
Section: Resultsmentioning
confidence: 99%